NEONATAL SCREENING TO BE INTENSIFIED IN MALAYSIA – APRM-ISNS 2015 - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 7 December 2015 The theme of the 9 Asia Pacific Regional Meeting for International Society for Neonatal Screening (APRMISNS) 2015, “New Insight in Neonatal Screening and The Way Forward” is both timely and appropriate, to bridge the knowledge gaps of the local participants with those from all over the world in the field of Neonatal Screening.